A Social Mission is Not Enough: Reflecting the Normative Foundations of Social Entrepreneurship - Ignas Bruder (Journal of Business Ethics, 2020)
Social entrepreneurship is not just an objective description of a phenomenon; it also carries a positive normative connotation. However, the academic discourse barely reflects social entrepreneurship's inherent normativity and often grounds it implicitly on the mission of a social enterprise. In this paper, we argue critically that it is insufficient to ground social entrepreneurship's inherent normativity on a social mission. Instead, we will show how such a mission-centric conception of social entrepreneurship, when put into practice, is prone to enhance rather than diminish societal grievances. In order to give social entrepreneurship an explicit and sound ethical grounding, we draw on integrative economic ethics as a frame of reference. From this perspective, social entrepreneurship necessitates adherence to the discourse-ethically reasoned moral principle in order to live up to its inherent normative validity claim of good entrepreneurship. The consideration of social entrepreneurship practices is crucial to make this approach less vulnerable to ethical critique. The addition of a practice dimension overcomes the mission-centric view of social entrepreneurship and opens up a typology of enterprise forms, thereby enabling a more fine-grained distinction between social enterprises and other forms of organization.
Keywords: 300; Normative critique of social entrepreneurship; Integrative economic ethics; Critique of economism; Social enterprise; Normativity; Discourse ethics; Typology